Numerical Calculation of Equivalent Permeability Tensor for Fractured Vuggy Porous Media Based on Homogenization Theory (Communications in Computational Physics, 2011)
A numerical procedure for the evaluation of equivalent permeability tensorfor fractured vuggy porous media is presented. At first we proposed a new conceptualmodel, i.e., discrete fracture-vug network model, to model the realistic fluid flow infractured vuggy porous medium on fine scale. This new model consists of three systems:rock matrix system, fractures system, and vugs system. The fractures and vugsare embedded in porous rock, and the isolated vugs could be connected via discretefracture network. The flow in porous rock and fractures follows Darcy's law, and thevugs system is free fluid region. Based on two-scale homogenization theory, we obtainedan equivalent macroscopic Darcy's law on coarse scale from fine-scale discretefracture-vug network model. A finite element numerical formulation for homogenizationequations is developed. The method is verified through application to a periodicmodel problem and then is applied to the calculation of equivalent permeability tensorof porous media with complex fracture-vug networks. The applicability and validityof the method for these more general fractured vuggy systems are assessed through asimple test of the coarse-scale model.